Laser ablation synthesis of Ag nanoparticles in graphene quantum dots aqueous solution and optical properties of nanocomposite - Sadrolhosseini, A.R. (2019)
In this study, silver nanoparticles were synthesized in a graphene quantum dots aqueous solution using the laser ablation method. A silver plate was ablated at different times, and silver nanoparticles formed in the graphene quantum dots solution at room temperature. The prepared samples were tested using these analytical methods. The graphene quantum dots surrounded the sphere-shaped silver nanoparticles; particle sizes ranged from 26.76 to 21.61Â nm. The silver nanoparticles interacted with the carboxyl and hydroxyl functional groups. The prominent and considerable property of the silver nanoparticles/graphene quantum dots composite was enhancement of the Raman scattering. The obtained scattered Raman intensity was nearly 6 times stronger than pure graphene quantum dots. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.